Frekuensi Konseling Gizi, Pengetahuan Gizi Ibu dan Perubahan Berat Badan Balita Kurang Energi Protein (KEP) di Klinik Gizi Puskesmas Kunciran Kota Tangerang - Cahyani, Fajar Nova; Hartono, Antonius Sri; Ngadiarti, Iskari (Jurnal Nutrire Diaita (Ilmu Gizi), 2010)
AbstractIndonesia still have four major nutritional problems, one of the problem is malnutrition of energy protein (KEP). The effectiveness and efficiency solving of nutritional problem are nutrition intervention such as supplementation, fortification and nutrition education. The aim of this study is to determine the relationship betwen the frequency of nutrition counseling, nutritional knowledge of mothers and variance of weight children under five years less energy protein at Clinical Nutrition of Community Health centre, Kunciran, Buraeu of Health, Tangerang City in 2008.Â  This is associative study with cross-sectional design. The population in this study is all infants who comes to community health centre refferal from POSYANDU and MTBS on Tuesday. The total sample of this study was 46 mothers. This study used Pearson Product Moment Correlation to analyze the data. Most of respondents aged 26-30 years (30.4%), the education level is primary school (43.5%), and unemployment or housewife (84.8%). Most of children under five years is female (67.4%) and aged 12-35 months (56.5%). The results shows that there was no relationship between frequency of nutrition counseling, nutritional knowledge of mothers, and variance of weight children under five years, the value of correlation respectively (0.109; 0,156; 0.170). The conclusion of this study is no relationship between the frequency of nutrition counseling, nutritional knowledge of mothers and variance of weight children under five years less energy protein. However, based on boxplot graphs shows there is a tendency among the frequency of nutrition counseling, nutritional knowledge of mothers and variance of weight children under five years less energy protein.Keywords: frequency of nutrition counseling, nutritional knowledge, variance of weightAbstrakIndonesia masih menghadapi empat masalah gizi utama, salah satunya adalah Kurang Energi Protein (KEP). Intervensi gizi melalui suplementasi, fortifikasi dan pendidikan gizi merupakan langkah penanggulangan masalah gizi yang memberikan hasil yang efektif dan efisien. Penelitian ini bertujuan untuk menganalisa hubungan antara frekuensi konseling gizi, pengetahuan gizi ibu dengan perubahan berat badan balita KEP di Klinik Gizi Puskesmas Kunciran Kota Tangerang. Jenis penelitian ini adalah asosiatif dengan pendekatan cross-sectional. Populasi dalam penelitian ini adalah seluruh balita KEP yang datang ke Klinik gizi Puskesmas Kunciran rujukan dari posyandu dan Klinik Manajemen Terpadu Balita Sakit (MTBS) pada hari Selasa, dan sampel didapat 46 orang ibu balita. Analisa data menggunakan Uji Pearson Product Moment Correlation. Sebagian besar responden berumur 26-30 tahun (30,4%), memiliki tingkat pendidikan SD (43,5%), dan tidak bekerja (84,8%), sebagian besar balita adalah perempuan (67,4%) dan berumur 12-35 bulan (56,5%). Hasil menunjukkan bahwa tidak ada hubungan antara ketiga variabel tersebut dengan nilai korelasi masing-masing (0.109, 0.156, dan 0.170). Tidak ada hubungan antara frekuensi konseling gizi, pengetahuan gizi ibu dengan perubahan berat badan balita KEP. Namun berdasarkan grafik boxplot ada tendensi antara frekuensi konseling gizi, pengetahuan gizi ibu dan umur balita dengan perubahan berat badan balita KEP.Kata kunci: frekuensi konseling gizi, pengetahuan gizi, perubahan berat badan